Opiate Dependence as an Independent and Interactive Risk Factor for Arterial Stiffness and Cardiovascular Ageing - A Longitudinal Study in Females - Reece, Albert Stuart (Elmer Press, 2013)
BACKGROUND: Despite intriguing observational cross-sectional data there are no longitudinal studies of opiate related arterial disease. As opiates act via P16INK4A/CDKN2A, and vascular ageing has been thought to be a surrogate for organismal ageing, the subject has far-reaching implications. METHODS: Pulse Wave Analysis (PWA) by radial arterial tonometry (SphygmoCor) was performed on control and opiate dependent patients. RESULTS: A total of 37 controls were compared with 93 opiate dependents. They were studied on 117 and 275 occasions respectively up to 1,797 days. The mean (± S.E.M.) ages were 38.72 ± 2.64 and 33.78 ± 0.90 years (P = 0.0260), 91.4% and 10.8% smoked (P < 0.0001). Body mass index rose more in controls (P = 0.0185) and in interaction with time (P = 0.0025). When controlled for time and BMI, opiate dependency status was shown to be associated with vascular age and central arterial stiffness and pressure indices (all P < 0.05). When repeated measures multiple regression was performed on all traditional cardiovascular risk factors, the opiate dose-duration interaction was significant and appeared in 12 terms in the final model. It was also independently significant (P = 0.0153). Opiate dose or duration appeared in a further 15 terms. The model was shown to be significantly improved by the inclusion of terms for opiate dependency (A.I.C. 71.10 v 54.31, P < 0.0001). CONCLUSION: These data confirm increased vascular stiffness and ageing in a longitudinal study, and thereby imply advanced organismal ageing. These multivariate studies are consistent with opiate dependency as an interactive and multivariate cardiovascular risk factor and emphasize the role of treatment duration.